Intertwining Retirement Education with Adult Education - CHAEWON YANG (Adult Education Research Conference, 2017)
This literature review aims to explore how adult education can intervene to create a more satisfactory retirement through retirement education. Specifically, it is focused how retirement education has use transformative learning theory to interpret retirement experiences.
Keywords: retirement education; transformative learning theory; transition to retirement